Cultura de segurança do paciente na perspectiva da equipe de enfermagem - Ana Paula Mousinho Tavares; Elaine Cristina Carvalho Moura; Fernanda Valéria Silva Dantas Avelino; Vanessa Caminha Aguiar Lopes; Lidya Tolstenko Nogueira (Rev Rene, 2018)
Objective: to evaluate the patient safety culture from the perspective of the nursing team. Methods: crosssectional design, survey-type inquiry performed with 221 nursing professionals from a University Hospital. The instrument used was the Hospital Survey on Patient Safety Culture. The Kolmogorov-Smirnov test, the Spearman’s correlation coefficient and the Cronbach’s alpha coefficient were used in the analyses. Results: the patient safety culture has been moderately developed; teamwork within units corresponded to a strong area (75.5%) and the nonpunitive response to errors corresponded to an area for improvement (47.0%). It was observed that the greater the impression of nonexistence of problems and adequacy of the implanted systems, the better the rating assigned to the hospital. Conclusion: patient safety culture is in the process of development; the dimension with more positive answers was teamwork within units and, the one with less positive answers was nonpunitive response to errors.